Contraceptive steroids increase cholesterol in bile: mechanisms of action - Kern, F; Everson, G T (Journal of lipid research, 1987)
Contraceptive steroids increase the risk of acquiring cholesterol gallstones. The factors responsible include an increase in cholesterol saturation of bile and an increase in rate of secretion of cholesterol into bile. The goal of this study was to investigate the mechanism(s) of these increases in biliary cholesterol. During the use of contraceptive steroids, cholesterol saturation of gallbladder bile and the amount of cholesterol secreted per mole of bile acid increased (P less than 0.05 and P less than 0.02, respectively). Cholesterol absorption, cholesterol synthesis, chylomicron remnant clearance, and the concentration of plasma and lipoprotein lipids were not altered by contraceptive steroids. Despite this apparent lack of effect, important correlations were present during steroid use. LDL (low density lipoprotein) cholesterol increased as dietary cholesterol increased (r = 0.58, P less than 0.025). Cholesterol synthesis correlated directly with VLDL cholesterol concentration (r = 0.64, P less than 0.01), biliary cholesterol secretion (r = 0.68, P less than 0.01) and with molar percent cholesterol in bile (r = 0.49, P = 0.06). Chylomicron remnant clearance also correlated with cholesterol secretion (r = 0.85, P less than 0.001). As either remnant uptake or synthesis increased, the effect of the other source of hepatic cholesterol on biliary cholesterol secretion diminished. These relationships were not observed in the same subjects when they were not taking the hormones. The findings suggest that both newly synthesized and dietary cholesterol contribute to the cholesterol secreted in bile. This is consistent with the hypothesis that cholesterol for secretion into bile and VLDL is derived from a common metabolic pool of free cholesterol. It is proposed that contraceptive steroids exert their effect on biliary cholesterol by increasing cholesterol entering the pool and/or by inhibiting hepatic ACAT (acylcoenzyme A:cholesterol acyltransferase) activity, a known effect of progesterone, so that an increase in free cholesterol entering the pool leads to an increase in output.